THE INFLUENCE OF THE MULTICULTURAL LEARNING MODEL ON PANCASILA EDUCATION SUBJECTS ON THE UNDERSTANDING OF STUDENTS' TOLERANCE ATTITUDES - Indah Utari; Muhlasin Amrullah; Vanda Rezania (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The multicultural learning model is an essential approach in the context of today's education, in the era of globalization where social and cultural diversity is an important aspect that needs to be considered. This model aims to help students develop an attitude of tolerance in addition to emphasizing the cognitive component or mastery of knowledge. The purpose of this study is to see how the use of multicultural learning models affects the understanding of grade IV students about tolerance in Pancasila Education lessons. The researcher used a single-group experimental design and quantitative methodology. 28 students at SD Negeri Sidokepung 1 were the subjects of this study. Data collection was carried out through a pretest to measure students' initial understanding and posttest after the implementation of learning with a multicultural model. Testing the validity and reliability of the instrument is the first step in data analysis. Furthermore, using SPSS software version 26, normality tests, paired sample t-test, and N-Gain tests were carried out. The results of the analysis showed a significant increase in the understanding of students' tolerance attitudes, with the result of an N-Gain value of 0.82 which was categorized as high/effective. This researcher concluded that the multicultural learning model is effective in increasing students' tolerance attitudes and encouraging understanding of social and cultural diversity in the surrounding environment. The findings of this study are expected to support inclusive education and encourage the development of a tolerant generation.